Modelo de um sistema de medição de desempenho auxiliado por tecnologias da Indústria 4.0 para a gestão de cadeias de suprimentos sustentáveis - Santos, Paulo Henrique Amorim (Universidade Federal de São Carlos, 2024)
Sustainable Supply Chain Management (SSCM) aims to minimize environmental impact and maximize profit and social well-being through sustainable practices. Given its complexity and the need to measure results, SSCM requires the support of a contemporary and multidimensional performance measurement system (PMS), aligned with strategic objectives common to the links in the supply chain. In parallel, the Fourth Industrial Revolution offers a range of digital technologies that promise to assist in the lifecycle of PMSs, making them more collaborative, agile, and flexible. Thus, the objective of this study is to propose a PMS model assisted by I4.0 technologies for SSCM. In this regard, PMSs are understood according to their resources, roles, and processes. SSCM is addressed considering the three dimensions of sustainability (environmental, economic, and social) and its various practices. Meanwhile, I4.0 technologies are investigated regarding their applicability in supporting PMS. To achieve the proposed objective, the research method used combines bibliographic methods (scientific mapping, systematic literature review, and content analysis), survey (conducted with experts in the areas), and the multi-criteria decision-making methods (MCDM) Fuzzy-VIKOR and Fuzzy-PROMETHEE. The thesis is structured as a compendium of articles, which aim to disseminate the bibliographic and empirical results of the methods used. The analyses and discussions developed in this thesis clarify how I4.0 technologies can be used in PMSs to achieve continuous improvement in SSCM practices. The developed model is directed at managers who seek a tool to achieve superior performance in SSCM, and who are willing to adapt to a new context of digitalization. Moreover, the work brings advances to the field and a research agenda for future references.
A performance measurement system model supported by Industry 4.0 technologies for sustainable supply chain management
Keywords: Sistemas de medição de desempenho; Indústria 4.0; Gestão da cadeia de suprimentos sustentável; Pesquisa de levantamento; Métodos de tomada de decisão multicritério; Performance measurement systems; Industry 4.0; Sustainable supply chain management; Survey; Multicriteria decision-making methods; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO